ANALISIS PENGARUH SISTEM ANGGARAN PARTISIPASIF, BUDAYA ORGANISASI DAN PERILAKU PIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PANGAN, KELAUTAN DAN PERIKANAN KABUPATEN BIREUEN - Fadhilah, Laina; Nazli, Cut Syamsiatun (LPPM-UNIKI, 2025)
Employee performance analysis is important to continuously observe in assessing performance-based work results. There are several factors related to it, including those conducted in this study. Using a questionnaire in collecting data on perceptions/assessments of the variables studied with quantitative research with a descriptive-associative type. Based on the perceptions of 60 employees of the Bireuen Regency Food, Maritime Affairs and Fisheries Service, it was found that (1) there is a causal relationship between the participatory budget system, organizational culture, and leadership behavior in working. (2) there is a direct and indirect influence, the three variables in supporting performance, where the participatory budget system has a total influence on performance of 28.6%, organizational culture has an influence of 46.6%, and leadership behavior has a total influence on employee performance of 23.07%. (3) The contribution of all three to employee performance is 41.5%.